Forensic Intelligence Based on Photo Image Analysis (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article continues the study of theoretical and practical aspects of such an information and analytical process as forensic intelligence. It is considered as a separate type of criminal analysis carried out by a person (subject) who has special knowledge in the field of forensic examination or with the involvement of such a person. Forensic intelligence based on photo image analysis combines elements of analytical, expert and operational-investigative activities, ensuring the systematisation and evaluation of criminally significant information to improve the effectiveness of investigations. The concept of “forensic intelligence based on the analysis of photographic images’’ is defined as a type of criminal analysis that involves the systematic collection, processing, evaluation and interpretation of visual data using specialised knowledge in the field of portrait and photographic expertise. It is emphasised that the involvement of an expert ensures the objectivity and evidential value of the results obtained. At the same time, automated recognition systems should be considered only as an auxiliary tool that requires mandatory expert verification. Domestic and foreign experience has been analysed, in particular the use of OSINT methods, artificial intelligence technologies and face recognition systems in forensic practice. The main stages of forensic investigation using photographic images have been identified, from the collection of materials and initial processing to their verification and the formation of analytical conclusions.It is concluded that the further development of this area requires the creation of a unified methodological base, improvement of interaction between analytical and expert units, expansion of technical capabilities and a system for training specialists. This will contribute to the formation of an effective national model of forensic intelligence that is compatible with international standards.